MITIGASI BENCANA BANJIR DENGAN PENERAPAN BIOPORI - Nugrahini Susantinah Wisnujati; Hary Sastrya Wanto; Sri Rahayu MJH; Rizky Junianto; Prama Hasta (JURNAL PENGABDIAN MANDIRI, 2022)
Sidoarjo Regency East Java Indonesia is influenced by Urban Sprawl from the growth of Surabaya City. Residential land is increasingly limited, land prices are increasingly expensive in Surabaya, so people are looking for settlements in suburban areas of Surabaya, such as Waru District and Taman District. Population growth in Sidoarjo Regency increases the need for land provision for the community which will have an impact on being prone to flooding. This is the background for the Master of Agribusiness Study Program, Faculty of Agriculture, Wijaya Kusuma University Surabaya as part of the Faculty of Agriculture to provide solutions by increasing public understanding, especially PKK women, to mitigate flood disasters by making biopore holes. Biopori is an alternative and simple technology for rainwater infiltration other than infiltration wells. This activity was carried out by socializing the benefits of biopori online due to the implementation of the Emergency Community Activity Restriction (PPKM) from July 3, 2021 to July 31, 2021 and extended again until August 2, 2021, followed by making biopori.